KUMPULAN PUISI KUAJAK KAU KE HUTAN DAN TERSESAT BERDUA KARYA BOY CANDRA SEBAGAI MATERI AJAR: GAYA BAHASA DAN DIKSI - Bella Ristiana Putri; Kundharu Saddhono; Atikah Anindyarini (Universitas Sebelas Maret, 2019)
The objectives of this research are to describe 1) the use of style in the poetry collection book of Kuajak Kau ke Hutan dan Tersesat Berdua by Boy Candra, 2) the use diction in the poetry collection book of Kuajak Kau ke Hutan dan Tersesat Berdua by Boy Candra, and 3) relevance between in the poetry collection book of Kuajak Kau ke Hutan dan Tersesat Berdua with poetry writing in grade 10 th Senior High School.This research used a purposive sampling techniques. In this research, the qualitative descriptive method used by the stylistics was used to describe the use language styles and diction. The source of this research data is a text document. Data collection technique in the form of interactive data analysis. The validaty data used the trianggulation data.The result show that (1) the use of language style found in the books Kuajak Kau ke Hutan dan Tersesat Berdua is comparative, affirmations, and contradictions language style. The most dominant language style is comparative language style of metaphor, (2) the use diction found in the poetry collection book is connotative and denotative. The most dominant of diction is konotative, and (3) The poetry collection book can be relevance as the teaching material for poetry writing in grade 10 th Senior High School.